Prebiotic Supplementation has Only Minimal Effects on Growth Efficiency, Intestinal Health and Disease Resistance of Westslope Cutthroat Trout Oncorhynchus clarkii lewisi Fed 30% Soybean Meal - Sealey, Wendy M.; Conley, Zachariah B.; Bensley, Molly (Frontiers in Immunology, 2015)
Prebiotics have successfully been used to prevent infectious diseases in aquaculture and there is an increasing amount of literature that suggests that these products can also improve alternative protein utilization and digestion. Therefore, the objective of this study was to examine whether prebiotic supplementation increased the growth efficiency, intestinal health and disease resistance of cutthroat trout fed a high level of dietary soybean meal. To achieve this objective, juvenile Westslope cutthroat trout (Oncorhynchus clarkii lewisi) were fed a practical type formulation with 0 or 30% dietary soybean meal with or without the commercial prebiotic (Grobiotic-A) prior to experimental exposure to Flavobacterium psychrophilum. Juvenile Westslope cutthroat trout (initial weight 7.8 g/fish ± standard deviation of 0.5 g) were stocked at 30 fish/tank in 75 L tanks with six replicate tanks per diet and fed their respective diets for 20 weeks. Final weights of Westslope cutthroat trout were affected by neither dietary soybean meal inclusion level (P=0.9582) nor prebiotic inclusion (P=0.9348) and no interaction was observed (P=0.1242). Feed conversion ratios were similarly not affected by soybean meal level (P=0.4895), prebiotic inclusion (P=0.3258) or their interaction (P=0.1478). Histological examination of the distal intestine of Westslope cutthroat trout demonstrated increases in inflammation due to both increased soybean meal inclusion level (P=0.0038) and prebiotic inclusion (P=0.0327) without significant interaction (P=0.3370). Feeding dietary soybean meal level at 30% increased mortality of F.psychrophilum cohabitation challenged Westslope cutthroat trout (P=0.0345) while prebiotic inclusion tended to decrease mortality (P=0.0671). These results indicate that subclinical alterations in intestinal inflammation levels due to high dietary inclusion levels of soybean meal could predispose Westslope cutthroat trout to F.psychrophilum infection.